2018
DOI: 10.1177/1932296818755797
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Acetaminophen Interference in a Novel Continuous Glucose Monitoring System

Abstract: Acetaminophen (APAP) can cause erroneously high readings in real-time continuous glucose monitoring (rtCGM) systems. APAP-associated bias in an investigational rtCGM system (G6) was evaluated by taking the difference in glucose measurements between rtCGM and YSI from 1 hour before to 6 hours after a 1-g oral APAP dose in 66 subjects with type 1 or type 2 diabetes. The interference effect was defined as the average post-dose (30-90 minutes) bias minus the average baseline bias for each subject. The clinically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 6 publications
3
45
2
Order By: Relevance
“…In the international XANTUS (XArelto on preveNtion of sTroke and non-central nervoUS system systemic embolism in people with non-valvular atrial fibrillation) registry, which included 6784 participants treated with rivaroxaban from 311 centres in Europe, Israel and Canada, the overall rate of ischaemic stroke/systemic embolism was 0.8 per 100 patient-years [5]. Lower incidence rate of major bleeding on rivaroxaban was also reported by Coleman et al [2] (2.7 per 100 patient-years) than in people with diabetes in the ROCKET-AF trial (3.79 per 100 patientyears) [4]. Major bleeding rates with rivaroxaban treatment were also low, at 2.1 events per 100 patient-years in the XANTUS study [5] and 3.0 per 100 patient-years in the Dresden NOAC registry [6].…”
Section: Doi: 101111/dme13685mentioning
confidence: 82%
See 3 more Smart Citations
“…In the international XANTUS (XArelto on preveNtion of sTroke and non-central nervoUS system systemic embolism in people with non-valvular atrial fibrillation) registry, which included 6784 participants treated with rivaroxaban from 311 centres in Europe, Israel and Canada, the overall rate of ischaemic stroke/systemic embolism was 0.8 per 100 patient-years [5]. Lower incidence rate of major bleeding on rivaroxaban was also reported by Coleman et al [2] (2.7 per 100 patient-years) than in people with diabetes in the ROCKET-AF trial (3.79 per 100 patientyears) [4]. Major bleeding rates with rivaroxaban treatment were also low, at 2.1 events per 100 patient-years in the XANTUS study [5] and 3.0 per 100 patient-years in the Dresden NOAC registry [6].…”
Section: Doi: 101111/dme13685mentioning
confidence: 82%
“…In a recent work published in Diabetic Medicine, Coleman et al [2] reported on their 'real-world' retrospective study which used US national MarketScan claims data. Their study included a large sample size of 11 034 people with AF, with a median 1.5 years of follow-up, and compared the performance of rivaroxaban with that of propensity-score matched warfarin (n=5517 in each arm).…”
Section: Doi: 101111/dme13685mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, one must exercise caution when taking acetaminophen or acetaminophen‐containing cold medications in persons using certain CGM devices that exhibit interference from these medications . Notably, some newer generations of CGM no longer experience acetaminophen interference …”
Section: The Effects Of Illness On Diabetesmentioning
confidence: 99%